Future robotic computer: A new type of computing device with robotic functions - Young-Ho Suh; Hyun Kim; Joo-Haeng Lee; Joonmyun Cho; Moohun Lee; Jeongnam Yeom; Eun-Sun Cho (2011 6th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2011)
With the advance of IT technologies, a new type of computing device will be introduced in our daily life in the near future. In this paper, we outline our on-going development of the robotic computer that naturally interacts with users, understands current situation about users and environments, and proactively provides users with services. We describe the system architecture and the implementation of a proof-of-concept prototype of the robotic computer proposed.